2016
DOI: 10.3747/pdi.2015.00062
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Antibiotics for Intraperitoneal Administration in Extraneal 7.5% Icodextrin Peritoneal Dialysis Bags (Stab Study)

Abstract: Antibiotics premixed in icodextrin PD-bags have varying stabilities with stability generally least at 37°C and best at 4(o)C, permitting storage for 14 days when refrigerated and prewarming to body temperature prior to administration. Further research confirming the sterility of these antibiotic-containing bags is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 12 publications
0
22
0
5
Order By: Relevance
“…The physico-chemical stability of ceftazidime in the absence of heparin in various types of PD solutions has been reported before (11,13,24,28). However, the results obtained in the current study after storing a ceftazidime-PD admixture at 4°C and 25°C cannot be compared with the results reported by previous studies due to the difference in methodological approach.…”
Section: Discussionmentioning
confidence: 65%
“…The physico-chemical stability of ceftazidime in the absence of heparin in various types of PD solutions has been reported before (11,13,24,28). However, the results obtained in the current study after storing a ceftazidime-PD admixture at 4°C and 25°C cannot be compared with the results reported by previous studies due to the difference in methodological approach.…”
Section: Discussionmentioning
confidence: 65%
“…Clinicians should remain alert for new studies in this area. In general, icodextrin-based PD solutions are compatible with vancomycin, cefazolin, ceftazidime, and gentamicin ( 329 , 333 , 334 ). When premixed in icodextrin solution, these antibiotics are least stable at 37°C and most stable at 4°C, permitting storage for 14 days when refrigerated and pre-warming to body temperature prior to administration ( 334 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Icodextrin is compatible with the commonly used intraperitoneal antibiotics, including cefazoline, ceftazidime, vancomycin, and gentamicin. 31,32 The impact of icodextrin use on peritonitis outcomes remains uncertain. In a randomized controlled trial among 53 adult CAPD patients, no significant differences were observed in terms of peritonitis cure or 120-day mortality between groups treated with icodextrin and treated with glucose-based PD solutions.…”
Section: Discussionmentioning
confidence: 99%